(untitled) (African Journal of Biomedical Research, 2023)
Diclofenac (DIC) is known to alter renal function in the form of hemodynamically-mediated acute renal failure. This study evaluated the protective role of the amino acid, glycine (Gly) on nephrotoxicity and acute hemodynamic alterations induced by DIC (9 mg/kg) in male Wistar rats. The rats were divided into four groups (n=7/group) including Group A (control); Group B (DIC-treated), Groups C (DIC + Gly1, 250 mg/kg) and Group D (DIC + Gly2 500 mg/kg). Systolic (SBP), diastolic (DBP) and mean arterial (MAP) blood pressures were significantly (p<0.05) reduced in rats treated with DIC alone, compared to control. Kidneys from DIC-treated rats showed altered histology with significantly (p<0.05) increased hydrogen peroxide (H2O2), malondialdehyde (MDA) and protein carbonyl contents, but decreased glutathione (GSH) glutathione peroxidase (GPx), glutathione S-transferase (GST) and superoxide dismutase (SOD) activities. Immunohistochemistry revealed down-regulation of renal angiotensin converting enzyme (ACE), but increased expressions of angiotensin type II receptor (AT2R) and mineralocorticoid receptor (MR) in DIC-treated rats. However, pre-treatment with Gly reversed most of the aforementioned effects of DIC. The present results suggest that oral glycine protected kidney tissues and restored DIC-induced hemodynamic changes by modifying renal expression of the renin-angiotensin-mineralocortocoid pathway and/or renal oxidative stress